2007
DOI: 10.1080/07420520701535795
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Suicide in Brazil

Abstract: Most of what is known about the seasonal variation in suicide rate originates from studies conducted in the northern hemisphere; very few studies have been done in the southern hemisphere. The purpose of the present study was to explore the possibility that in Brazil, the seasonal variation of suicides is a function of photoperiod. This was accomplished by analyzing monthly suicide data for a 12 yr period (1979 to 1990), within latitudes ranging from 2 degrees N to 33 degrees S. Single cosinor analyses with pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 44 publications
2
22
1
3
Order By: Relevance
“…For the State of São Paulo and other regions, no identifiable seasonal annual pattern was evident. 17 The findings of the present study were in line with those from studies of the temperate zone in the Northern hemisphere and suggest that suicide seasonality is linked only to localities situated in the climatic temperate zone, where the four seasons of the year are quite distinct. The States of Paraná, Santa Catarina and Rio Grande do Sul are situated in the temperate zone of the globe, since they are South of the Tropic of Capricorn.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…For the State of São Paulo and other regions, no identifiable seasonal annual pattern was evident. 17 The findings of the present study were in line with those from studies of the temperate zone in the Northern hemisphere and suggest that suicide seasonality is linked only to localities situated in the climatic temperate zone, where the four seasons of the year are quite distinct. The States of Paraná, Santa Catarina and Rio Grande do Sul are situated in the temperate zone of the globe, since they are South of the Tropic of Capricorn.…”
Section: Discussionsupporting
confidence: 79%
“…The States of Paraná, Santa Catarina and Rio Grande do Sul are situated in the temperate zone of the globe, since they are South of the Tropic of Capricorn. The difference observed between the results presented by Benedito-Silva et al 17 and the present study might be explained by methodological differences. However, the result of a seasonality trend observed in the male sample might reinforce the hypothesis that suicide seasonality depends on the latitude of the studied region, with intermediate results in tropical regions, as was observed by our study in the city of São Paulo.…”
Section: Discussioncontrasting
confidence: 57%
“…Por otro lado, un aspecto pobremente estudiado respecto a la conducta suicida en niños y adolescentes es su incidencia en las diferentes épocas del año o estacionalidad. Estudios en población adulta sobre el tema, asocian el patrón estacional del suicidio a la presencia de psicopatología, trastornos del ánimo, latitud, género y letalidad, entre otros [16][17][18][19] . En Chile, Heerlein et al muestran la existencia de un peak primaveral en suicidio en ambos sexos, en función del fotoperíodo 20 .…”
unclassified
“…[13][14][15] Since then, review studies, most performed in the Northern Hemisphere in mid-latitudes and developed nations, have continued to describe this pattern. 7,8 In Brazil, Benedito-Silva et al 16 found a seasonal distribution of suicide, peaking in spring/summer, but only in the southern states. Specifically in the city of São Paulo, Bando and Volpe reported a significant circannual cycle peaking in spring/summer for both men and women from 1996 to 2010, 17 while Nejar et al 18 did not find seasonality or any association between suicide and meteorological factors in São Paulo from 1996 to 2004.…”
Section: Introductionmentioning
confidence: 99%